Nanomaterials in the Prevention, Diagnosis, and Treatment of Mycobacterium Tuberculosis Infections. Issue 1 (21st September 2017) - Xu, Kaijin; Liang, Zhen Chang; Ding, Xin; Hu, Haiyang; Liu, Shaoqiong; Nurmik, Martin; Bi, Sheng; Hu, Feishu; Ji, Zhongkang; Ren, Jingjing; Yang, Shigui; Yang, Yi Yan; et al.
Abstract: Despite the tremendous advancements that have been made in biomedical research, Mycobacterium tuberculosis (TB) still remains one of the top 10 causes of death worldwide, outpacing the Human Immunodeficiency Virus as a leading cause of death from an infectious disease. In the light of such significant disease burden, tremendous efforts have been made worldwide to stem this burgeoning spread of disease. The use of nanomaterials in TB management has increased in the past decade, particularly in the areas of early TB detection, prevention, and treatment. Nanomaterials have been proven to be efficacious in the rapid and accurate detection of TB pathogens. Novel nanocarriers have also shown tremendous promise in improving drug delivery, potentially enhancing drug concentrations in target organs while at the same time, reducing treatment frequency. In addition, the engineering of antigen nanocarriers represents an exciting front in TB research, potentially paving the way for the successful development of a new class of effective TB vaccines. This article discusses epidemiology and pathogenesis of TB infections, current TB therapeutics, advanced nanomaterials for anti‐TB drug delivery, and TB vaccines. In addition, challenges and future perspectives in developing safe and effective nanomaterials in TB diagnosis and therapy are also presented. Abstract : The use of nanomaterials in mycobacterium tuberculosis (TB) detection, treatment, and prevention has made significant progress in the past decade. This review discusses nanomaterials for rapid and accurate detection of TB pathogens, nanocarriers for enhancing anti‐TB drug concentrations in target organs, and antigen nanocarriers as effective TB vaccine adjuvants.